Analysis of Sharia Economic Law on Vehicle Pawning in PT. Pegadaian (Persero) Cabang Bima, Nusa Tenggara Barat, Indonesia - Amrin, Amrin; Priyono, Adi; Shofita, Nailis (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2022)
This study aimed to examine the concept and system of vehicle pawning with a review of Sharia economic law. The research used descriptive qualitative with the type of field research at the Pawnshop Branch Office of the City of Bima, West Nusa Tenggara Province. While the data collection techniques were interviews, observations and documentation with data analysis using data reduction, data presentation and conclusion. The results show that, first, the practice of vehicle pawning financing products at the Bima City Pawnshop is relatively easy and practical. The view of Islamic law on vehicle pawning practices at the Bima City Pawnshop is considered to be by Sharia principles because it does not contain 3 elements that are prohibited in the practice of vehicle pawning. Such as Gharar, Maysir, and Sury. Because the suitability of the application for pawning vehicles at the Bima City Branch can be seen in three things, namely the pillars, the legal requirements for the pawn, the costs and the mechanism for the settlement of collateral goods. And the practice of pawning vehicles at the Bima City Pawnshop is governed by the Fatwa of the National Sharia Council No.26/DSN-MUI/III/2002 concerning Rahn Emas or similar items such as Vehicles.